An Integrated Approach to Temporal Monitoring of the Shoreline and Basin of Terkos Lake - Bayram, Bulent; Seker, Dursun Zafer; Acar, Ugur; Yuksel, Yalcin; Guner, H. Anil Ari; Cetin, Ibrahim (COASTAL EDUCATION & RESEARCH FOUNDATION, 2013)
In this study, the combinatorial shoreline and land-use/cover (LULC) changes in the shoreline and basin of Terkos Lake were examined using Landsat satellite images taken in 1986, 2001, and 2009. Terkos Lake is one of seven freshwater-supplying reservoirs of Istanbul, and its borders are very close to the Black Sea. Terkos Lake is in danger because of the approach of its borders to the Black Sea. Changes in the lake's shoreline have been measured using an algorithm based on a hybrid region growing image-segmentation method. The LULC changes have been monitored using object-oriented image-processing software to provide understanding of the impact of these changes on the shoreline. Overall accuracy of the classification reached 92% for 1986, 94% for 2001, and 93% for 2009. The maximum shoreline change measured was 280 m in 23 years. Also, the obtained shoreline and LULC changes have been integrated into the long-term analysis of wave and wind characteristics and sediment-transport calculations. The calculations have been validated with shoreline changes, which have been automatically extracted from Landsat satellite images. The basic outcomes and proposals have been suggested to deal with uncontrolled human activities in the study area.
Keywords: Automatic shoreline extraction; object-oriented classification; remote sensing; image processing; coastal monitoring; WATER RESERVOIR; CLASSIFICATION; ISTANBUL; Environmental Sciences & Ecology; Physical Geography; Geology